Increased TNF serum levels are related to highly aggressive behavior in male Swiss Webster mice (Global Journal of Medical Research, 2014)
Since the 1960s, mouse behavior has been systematically studied in the laboratory environment; however, there is still no consensus regarding the causes of aggression in laboratory animals. The involvement of the immune response in aggressive animal behavior has not been well elucidated. Different studies have found that the levels of interferon alpha (IFN-α), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α) are elevated in depressogenic/anxiogenic models. The aim of this study is to assess the correlations of serum cytokine (TNF, IL-6 and IL-10) levels with patterns of aggressive behavior (PBA). Our results suggest that mice exhibiting anxiety-like and highly aggressive behaviors have increased TNF serum levels and slightly decreased IL-10 levels. Additionally, a direct correlation was observed between high PBA scores and increased levels of TNF.
Keywords: aggressive behavior; laboratory mice; cytokine levels